Factors Influencing the Greenhouse Gas Emissions Disclosure at Manufacture Company in the Indonesia Stock Exchange - Frida Christin Natalia; Andewi Rokhmawati; Yulia Efni (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
This study aims to examine empirically the factors that influence greenhouse gas emission disclosure. Factors examined in this research are a type of industry, firm size, profitability, and leverage. In this study, the researcher adopted the checklist issued by the Carbon Disclosure Project (CDP) to measure the extensive disclosure of greenhouse gas emissions. To examine the factors, the researcher utilized multiple regression. The population of this study was all manufacturing companies listed on the Indonesian Stock Exchange in 2018. This research applied the purposive sampling method to obtain 131 listed manufacturing in 2018. The result implies that firm size has a positive and significant correlation with greenhouse gas emission disclosure. Meanwhile, type of industry, profitability, and leverage had no significant correlation with greenhouse gas emission disclosure. Manufacturing companies, especially greenhouse gas-intensive companies, must participate in protecting the environment and help reduce greenhouse gas emissions as stipulated in Presidential Regulation No. 61 of 2011 concerning the National Action Plan for Reducing Greenhouse Gas Emissions. In line with the concept of performance measurement of "Triple Bottom Line," the company does not only pay attention to profit (profit) and people (social), the company must also pay attention to the planet (environment). So the company can compete with other companies. The results highlighted that the much resources of the company, the better the company is conducting a greenhouse-gas-emission reduction strategy. It makes it easier for the company to do the disclosure of greenhouse gas emissions.